PENGARUH JUMLAH KUNJUNGAN WISATAWAN, JUMLAH AKOMODASI DAN JUMLAH OBJEK WISATATERHADAP PENDAPATAN PROVINSI KEPULAUAN BANGKA BELITUNG - Melsy Nanda Sukma, - (2019)
This study aims to determine the effect of Number of Tourist Visits, Number of Accommodations and Number of Tourist Objects to Tourism Sector Revenue in districts in the Province of Bangka Belitung Islands in 2010-2014. The data used is time series data from the publication of the Statistical Center and The Tourism Office of the Province of Bangka Belitung Island. This research uses quantitative research method. The technique of determining the sample using purposive sampling method. Hypothesis testing in this study used Multiple Linear Regression Analysis with SPSS 23 program and 5% significance level (0,05). The results of this study showed that the Number of Tourist Visits has a significant influence on Tourism Sector Revenue with significance level of 0.001 lower than the significance level specified α = 0.05, while for the Number of Accommodation has no significant influence on Tourism Sector Revenue with significance level of 0.753 greater than the specified significance level α = 0.05 and also Number of Tourism Object has an insignificant influence to the Tourism Sector Revenue Rate with significance level of 0.256 greater than the significance level specified α = 0.05. Limitations of this study are based on data obtained from the source indicates that there is still a lot of data that is incomplete so that the less the sample in the study.